A convenient synthesis of phthalocyanines bearing four methyl 4-hexyloxyphenyl-2-phenoxy acrylate functionalities - (:unkn) unknown (Society of Porphyrins and Phthalocyanines (SPP), 2009)
A novel synthetic pathway for the preparation of a new phthalonitrile derivative, methyl (E)-3-[2-(3,4-dicyanophenoxy)-4-(hexyloxy)phenyl]acrylate (3), based on the opening of the lactone ring of 7-hexyloxycoumarin (2H-1-benzopyrane-2-one, 2H-chromen-2-one) and ether formation of the formed hydroxy group with 4-nitrophthalonitrile, is presented. Cyclotetramerization of this dinitrile in 2-N,N-dimethylaminoethanol gives the desired Zn(II), Co(II) and Cu(II) phthalocyanines (4, 5 and 6) with four methyl 4-hexyloxy-2-phenoxy acrylate moiety on periphery. The complexes are characterized by IR, elemental analysis, 1H NMR, 13C NMR MALDI-TOF and UV-vis spectroscopy. The redox behavior of the complexes are also discussed. © 2009 World Scientific Publishing Company.
Keywords: 7-hydroxycoumarin (umbelliferone); Electrochemistry; Metallophthalocyanines; Phenyl acrylate